Cytokine profiles in maternal serum are candidates for predicting an optimal timing for the delivery in early‐onset fetal growth restriction. (14th March 2020) - Kawashima, Akihiro; Oba, Tomohiro; Yasuhara, Rika; Sekiya, Bunbu; Sekizawa, Akihiko
Abstract: Objective: We examined whether maternal serum cytokine profiles of mothers with early‐onset fetal growth restriction (FGR) were associated with delivery within 2 weeks after sampling during the third trimester. Study design: This exploratory prospective cross‐sectional study included a total of 20 singleton fetuses with early‐onset FGR and 31 healthy controls. Maternal serum samples during the early third trimester were analyzed for 23 cytokines. Results: Of 20 fetuses with early‐onset FGR, 14 had delivery within 2 weeks after sampling. Multivariate analysis revealed that maternal serum concentrations of soluble vascular endothelial growth factor receptor‐1 (sVEGFR‐1) and soluble CD40 ligand (sCD40L) were independently associated with delivery within 2 weeks in early‐onset FGR. Among cases of early‐onset FGR, concentrations of almost all maternal serum cytokines were similar. Maternal serum sVEGFR‐1 concentrations were high when delivery occurred within 2 weeks. Maternal serum sCD40L concentrations were elicited only in cases in which delivery within 2 weeks occurred due to fetal deterioration. Conclusion: We identified two biomarkers, one specific for FGR and the other dependent on severity, that were significant components of angiogenic activities and inflammation factors. Imbalances in serum protein expression may have a substantial effect on the pathogenesis of FGR.